Recent Advances in Miniaturized Microextraction Techniques for the Determination of Bisphenols in Environmental Samples: An Overview of the Last Two Decades - Tsalbouris, Athanasios; Kalogiouri, Natasa P.; Samanidou, Victoria F. (Current Analytical Chemistry, 2021)
Background: Bisphenols are major industrial chemicals that have raised public concern due to their endocrine disrupting properties and toxicity. Sample preparation is the most critical step for the determination of bisphenols, especially if the analyst has to deal with environmental samples which are complex matrices and the co-extraction and co-elution of other relevant compounds results in the enhancement or suppression of the analyte signal. The need for the precise determination of bisphenols has signaled the development of effective microextraction techniques according to the Green Analytical Chemistry (GAC) guidelines. Objective: The objective of this review is to gather and discuss all the recent advances in the development of microextraction techniques such as solid phase extraction (SPE), solid phase microextraction (SPME), magnetic solid phase microextraction (MSPE), liquid-phase microextraction (LPME), dispersive liquid-liquid microextraction (DLLME), stir bar sorptive extraction (SBSE), and matrix solid-phase dispersion (MSPD), that have been successfully applied in the extraction of bisphenols from environmental matrices. Conclusion: The analytical performance of the proposed techniques is critically discussed, highlighting the potential and the limitations of each method.
Keywords: environmental samples